The International Aspect of the Establishment of the State of Palestine - Avad. Zaully (Vestnik MGIMO-Universiteta)
From the very beginning of the Middle East conflict the relations between the Israelis and the Palestinians as well as the problem of establishing a Palestinian state have gone far beyond the region to become an issue of the international political agenda. The internationalization of the Palestinian statehood problem was a gradual process of more and more regional and international actors getting involved. Undoubtedly, the UN has played one of the major roles in the Middle East settlement. The European, Russian, Arab and American participation has been of a certain importance as well.